2013
DOI: 10.1007/s11255-013-0608-7
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation through a modified non-muscle-cutting Pfannenstiel incision

Abstract: In the era of minimally invasive surgery, MFI technique could challenge the role of laparoscopic and robotic surgery in renal transplantation. Our study shows that the technique is successful in carefully selected patients with low BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Patients without morbid obesity deserve well of minimally invasive renal transplantation in the retroperitoneum, where the risk of percutaneous renal biopsy was minimal [20,21]. However, patients of low BMI, as Keshore et al [22] reported to be 20 AE 2.9 kg/m 2 , might have incisions of 13 AE 1.7 cm in length allowing vascular anastomoses after placing the renal grafts in the retroperitoneal space. We would maintain that robotic assistance which provided relatively ample operation space and full range of sewing motion could benefit a renal transplant patient through an even smaller skin incision (7.7 AE 1.04 cm in our series).…”
Section: Discussionmentioning
confidence: 99%
“…Patients without morbid obesity deserve well of minimally invasive renal transplantation in the retroperitoneum, where the risk of percutaneous renal biopsy was minimal [20,21]. However, patients of low BMI, as Keshore et al [22] reported to be 20 AE 2.9 kg/m 2 , might have incisions of 13 AE 1.7 cm in length allowing vascular anastomoses after placing the renal grafts in the retroperitoneal space. We would maintain that robotic assistance which provided relatively ample operation space and full range of sewing motion could benefit a renal transplant patient through an even smaller skin incision (7.7 AE 1.04 cm in our series).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation (KT) stands as the foremost treatment for individuals with end-stage renal disease (ESRD), offering an enhanced quality of life and extended life expectancy when compared to dialysis 1 . Despite the heightened morbidity and increased risk of surgical site infection 2 , 3 , the open surgical approach has remained the standard procedure for KT since its inaugural success in 1954 4 . While minimally invasive surgical techniques in open kidney surgery have been suggested 5 and are employed in some clinical settings 6 , they aren’t suitable for ESRD patients with obesity.…”
Section: Introductionmentioning
confidence: 99%
“… 9 discovered that maintaining rewarming time under 50 min using the Vattikuti Urology Institute-Medanta Technique (VUIMT) can prevent any impairment of renal function. Although some high-volume centers have reported a median rewarming time of less than 50 min 2 , 10 , achieving this goal can be challenging and may require at least 35 cases 14 . Another strategy to mitigate the negative effects of rewarming is by keeping the graft at a lower temperature.…”
Section: Introductionmentioning
confidence: 99%